Stimuli-responsive polyelectrolyte surfactant complexes for the reversible control of solution viscosity. Issue 12 (11th March 2022) - Del Sorbo, Giuseppe Rosario; Clemens, Daniel; Schneck, Emanuel; Hoffmann, Ingo
Abstract : A pH sensitive surfactant with an oppositely charged polyelectrolyte allows the reversible control of solution viscosity through aggregate formation. Abstract : Interactions of polyelectrolytes with oppositely charged surfactants can give rise to a large variety of self-assembled structures. Some of these systems cause a drastic increase in solution viscosity, which is related to the surfactant forming aggregates interconnecting several polyelectrolyte chains. For these aggregates to form, the surfactant needs to be sufficiently hydrophobic. Here, we present a system consisting of the anionic surfactant sodium monododecyl phosphate and the cationic cellulose-based polyelectrolyte JR 400. The hydrophobicity of the surfactant can be controlled by the solution's pH. At pH > 12, the surfactant headgroup bears two charges. As a consequence, the solution viscosity decreases drastically by up to two orders of magnitude, while it can be as high as 10 Pa s at lower pH. In this paper, we investigate the changes of the mesoscopic structure of the system which lead to such drastic changes in viscosity using small angle neutron scattering and neutron spin-echo spectroscopy. Such systems are potentially interesting as they allow for a modular design where stimuli responsiveness is introduced by relatively small amounts of surfactant reusing the same simple polyelectrolyte.